When Girls Lead: Changing the Playbook for Climate Justice. Issue 2 (1st June 2022) - Huang, Tsun-Chueh; Bent, Emily
Abstract: Greta Thunberg's prominence in the climate justice movement symbolically positions girls at the epicenter of geopolitical resistance, but, while she is given immediate authority across media outlets, other girls' visions of a more equitable future are often disregarded; this demands our careful attention. We discuss the work of five New York City-based girl activists of color engaged in this movement. We explore the ways in which their intersectional identities and social positions shape their mobilization strategies and draw connections to other popular social justice movements; their activist playbook reveals the transformative potential of intersectional feminist politics in the hands of Generation Z. These girl activists of color generate sophisticated, relational platforms for climate justice informed by the interconnected issues of racial and economic injustice.